A historical-critical analysis of the Church of England in South Africa’s historiographical claim of apoliticism during apartheid (1948-1994) - Van der Merwe, J.M. (Johan Matthys) (University of Pretoria, 2023)
Dissertation (MTh)--University of Pretoria, 2023.